Inhibition of Activity of GABA Transporter GAT1 by δ-Opioid Receptor. (25th December 2012) - Pu, Lu; Xu, Nanjie; Xia, Peng; Gu, Quanbao; Ren, Shuanglai; Fucke, Thomas; Pei, Gang; Schwarz, Wolfgang
Abstract : Analgesia is a well-documented effect of acupuncture. A critical role in pain sensation plays the nervous system, including the GABAergic system and opioid receptor (OR) activation. Here we investigated regulation of GABA transporter GAT1 by δ OR in rats and in Xenopus oocytes. Synaptosomes of brain from rats chronically exposed to opiates exhibited reduced GABA uptake, indicating that GABA transport might be regulated by opioid receptors. For further investigation we have expressed GAT1 of mouse brain together with mouse δ OR and μ OR in Xenopus oocytes. The function of GAT1 was analyzed in terms of Na + -dependent [ 3 H]GABA uptake as well as GAT1-mediated currents. Coexpression of δ OR led to reduced number of fully functional GAT1 transporters, reduced substrate translocation, and GAT1-mediated current. Activation of δ OR further reduced the rate of GABA uptake as well as GAT1-mediated current. Coexpression of μ OR, as well as μ OR activation, affected neither the number of transporters, nor rate of GABA uptake, nor GAT1-mediated current. Inhibition of GAT1-mediated current by activation of δ OR was confirmed in whole-cell patch-clamp experiments on rat brain slices of periaqueductal gray. We conclude that inhibition of GAT1 function will strengthen the inhibitory action of the GABAergic system and hence may contribute to acupuncture-induced analgesia.